Fostering mindfulness : building skills that students need to manage their attention, emotions, and behavior in classrooms and beyond - Murphy, Shelley (Shelley Leigh) (Pembroke Publishers, 2019)
"A guide for teachers on how to incorporate simple mindfulness activities and strategies to help foster self-regulation in the classroom and beyond. The book defines self-regulation as students' ability to manage their own attention, emotions and behaviour. Teachers are invested in learning how to help students strengthen their attention-regulation, emotion-regulation and behaviour-regulation skills. Instructions, scripts, worksheets and ready-to-use templates complement this timely book."--